MEMBANTU MENINGKATKAN PELAYANAN POSYANDU DI DESA KURIPAN KABUPATEN LOMBOK BARAT OLEH KKN UMMAT-37 2023 - Hidayat, Rahmad; Badi'ah, Novita Riadhul; Hartiani, Dina; Yanti, Yanti; Ulandari, Ilna; Kusuma, Lia (Madiun Spoor : Jurnal Pengabdian Masyarakat, 2023)
Posyandu is a form of activity in order to fulfill basic health which is carried out from, by and for the community and collaborates with health authorities in a place. The aim of implementing this activity is to increase the effectiveness of posyandu services and analyze the shortcomings of posyandu services. The method used is divided into 3 stages, namely planning, preparation and implementation. The research results show that posyandu services are running quite well and are regularly implemented. From the results of service activities, it shows that posyandu services are running quite well and are regularly carried out. There are several obstacles in posyandu services, namely convolutedness, lack of posyandu cadres, and lack of coordination with the community. Keywords: posyandu, service, effectivenes